Composite gel for remineralization of dog enamel and preparation method and application thereof
By optimizing the composite gel formulation of CPP-ACP and nBG and diode laser irradiation, a porous cluster structure was formed, which solved the problem of low remineralization efficiency of canine tooth enamel in the existing technology and improved mechanical properties and remineralization effect.
Patent Information
- Application Number
- CN202511835348.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-08
- Publication Date
- 2026-02-10
AI Technical Summary
In existing technologies, single casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) has limitations in repairing the mechanical properties and mineral structure of canine enamel, and the concentration and nucleation rate of diode laser therapy and nano-bioactive glass (nBG) affect the repair effect, lacking an efficient combination scheme.
A composite gel formulation containing a specific ratio of CPP-ACP and nBG was developed. Through an optimized preparation method and diode laser irradiation, a porous cluster structure was formed. Combined with laser treatment, the remineralization efficiency and mechanical properties of canine tooth enamel were improved.
Without damaging the tooth structure, it significantly improves the remineralization efficiency and mechanical properties of canine enamel, reduces the risk of dentin exposure, forms a stable composite material structure, and achieves excellent remineralization results.
Smart Images

Figure CN121489795A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of veterinary oral care materials and technology, specifically relating to a composite gel preparation for caring for and enhancing the mechanical properties of canine tooth enamel, a preparation method containing the gel preparation, and a treatment method for using it in conjunction with a diode laser. Background Technology
[0002] Canine enamel, as the outermost layer covering the crown, possesses excellent mechanical strength and wear resistance, making it a crucial structure for maintaining oral function and health in dogs. However, due to factors such as chewing hard foods, toys, or enamel developmental abnormalities, dogs often experience varying degrees of enamel wear and defects, leading to clinical problems such as dentin exposure, pulp infection, and periodontal disease. Currently, there is considerable research on enamel remineralization in human medicine, but less research and application in animals. Furthermore, remineralization therapy, as an important non-invasive strategy for repairing demineralized enamel, has been widely used in human oral clinical practice.
[0003] Remineralization therapy aims to provide calcium (Ca) 2+ ), phosphate (PO4) 3- Casein phosphopeptide-amorphous calcium phosphate complex (CPP-ACP) is an effective remineralizing agent, which stabilizes the calcium in ACP through CPP. This process allows mineral ions such as calcium to deposit on the demineralized glaze surface, restoring its mineral structure and mechanical properties. 2+ and PO4 3- Ions enhance the retention and penetration of ions on the glaze surface. However, single CPP-ACP has limitations in repairing deep demineralization and significantly improving the mechanical properties of glazes.
[0004] Nano-bioactive glass (nBG) is another promising remineralization material, whose main component is dicalcium silicate (Ca2SiO4), and its crystal structure is SiO2-CaO-P2O5. nBG can rapidly release Ca2+ in the oral environment. 2+ and PO4 3- The ions can form a silica gel layer, which serves as a nucleation site for hydroxyapatite (HAP) and synergistically promotes mineralization. However, the concentration of nBG has a significant impact on its nucleation rate and the density of the deposited layer; an inappropriate concentration may lead to poor remediation results.
[0005] Low-energy laser therapy (LLLT), particularly diode lasers, has been shown to enhance enamel's resistance to acid and promote the efficacy of remineralizing agents. Its mechanisms may include reducing enamel solubility, modulating ion channels, and improving the permeability of composite gels.
[0006] Currently, there are no reports on combining a specific ratio of CPP-ACP with nBG and further integrating it with a diode laser with optimized parameters specifically for canine enamel restoration. Therefore, developing a combined approach that can efficiently restore the mechanical properties and mineral structure of canine enamel, combining the advantages of ion release and structure induction to improve remineralization efficiency, and addressing the limitations of single-material treatments in repairing deep demineralization and enhancing the mechanical properties of enamel, has significant clinical significance and application value. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention develops a simple and effective method for preparing a CPP-ACP / nBG composite gel formulation with optimal mechanical properties. Combined with diode laser irradiation of different intensities, this method restores the physiological mineralization structure of enamel without damaging tooth tissue, thereby improving mechanical properties and reducing the risk of dentin exposure. This solves the problems of low remineralization efficiency and limited improvement in the mechanical properties of enamel in existing technologies.
[0008] In a first aspect, the present invention provides a composite gel CPP-ACP / nBG for remineralization of canine enamel, comprising casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and active nanoglass (nBG). In the composite gel, the content of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) is 5-15 wt%, and the content of active nanoglass (nBG) is 3-10 wt%.
[0009] Furthermore, the composite gel contains 10 wt% CPP-ACP and 6 wt% nBG.
[0010] Furthermore, the composite gel has a porous cluster structure, wherein the Ca / P molar ratio is 1.8-2:1.
[0011] Furthermore, the composite gel structure has a rough surface and is rich in micropores, which is conducive to the retention and release of mineral ions, thereby significantly improving remineralization efficiency. The Ca, P, Si, and O elements are uniformly distributed in the composite gel, and CPP-ACP and nBG achieve the fusion of functional groups without destroying their respective structures, forming a composite material with good bioactivity and structural stability.
[0012] A second aspect of the present invention provides a method for preparing the composite gel described in the first aspect, comprising the following steps: (1) Preparation of casein phosphopeptide-amorphous calcium phosphate complex (CPP-ACP): S1. Enzymatically hydrolyze casein solution to obtain casein phosphopeptide (CPP) solution; S2. Prepare calcium ion solution A and phosphate ion solution B respectively; Further, in step S1, casein is dissolved in water, the pH is adjusted to 7-9, and trypsin is added for enzymatic hydrolysis. After enzymatic hydrolysis, the pH is adjusted to 4.0-4.8, a precipitate appears in the solution, and after centrifugation, an 8%-15% w / v casein solution is prepared.
[0013] Furthermore, the concentration of the casein aqueous solution is 80-120 mg / mL.
[0014] Furthermore, the enzymatic hydrolysis temperature is 35-50℃, and the enzymatic hydrolysis time is 8-16 h.
[0015] Furthermore, the amount of trypsin added is 5-10 wt% of casein.
[0016] Furthermore, glycerol and 1,2-propanediol are also added during the enzymatic hydrolysis process.
[0017] Furthermore, the amount of glycerol added is 5-10 wt% of trypsin.
[0018] Furthermore, the amount of 1,2-propanediol added is 1-3 wt% of trypsin.
[0019] Specifically, in step S1, casein is dissolved in water, the pH is adjusted to 7-9, and trypsin, glycerol and 1,2-propanediol are added for enzymatic hydrolysis. After enzymatic hydrolysis, the pH is adjusted to 4.0-4.8, a precipitate appears in the solution, and after centrifugation, an 8%-15% w / v casein solution is prepared.
[0020] Furthermore, the pH value of the system was adjusted using 1-3 mol / L hydrochloric acid.
[0021] The inventors discovered that during enzymatic hydrolysis, glycerol, as a typical enzyme activity protectant for trypsin, can effectively improve enzymatic hydrolysis efficiency. The addition of 1,2-propanediol plays a dual role: during enzyme activation, 1,2-propanediol molecules interact with enzyme molecules through hydrogen bonds, providing a more stable microenvironment for the enzyme protein in the hydrolysis environment, effectively reducing enzyme inactivation and loss, and ensuring the continuity and stability of catalytic efficiency. Both provide strong support for the enzymatic hydrolysis to obtain casein activity. Simultaneously, in the CPP-ACP co-precipitation stage, 1,2-propanediol may also act as a structure-directing agent, guiding amorphous calcium phosphate (ACP) to stack with casein phosphopeptide (CPP) as a template by regulating the solid-liquid interface energy, thereby constructing and stabilizing its porous cluster structure. The synergistic use of the composite protectants provides a strong guarantee for the efficient and stable preparation of CPP-ACP complexes with ideal structures.
[0022] In one embodiment of the present invention, 25 g of casein solid was dissolved in 250 mL of distilled water, stirred with a magnetic stirrer until dissolved, and then dissolved with 1 mol·L⁻¹ water. -1 The pH of the mixed solution was adjusted to 8.00 using NaOH solution. 2 g of trypsin, 0.1 mL of glycerol, and 0.05 mL of 1,2-propylene glycol were added to this solution, and the mixture was stirred and incubated at 45°C for 12 h. After enzymatic hydrolysis, the pH was adjusted to 4.0-4.8, and a precipitate formed. The precipitate was centrifuged at 3000 rpm at 25°C for 20 min, and dissolved in sterile deionized water to prepare a 10% w / v casein solution.
[0023] Further, in step S2, solution A is one or more of potassium dihydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate aqueous solution; solution B is one or more of calcium chloride, calcium nitrate, and calcium sulfate aqueous solution.
[0024] Furthermore, in step S2, the molar ratio of calcium to phosphorus (Ca:P) in solution A and solution B is 2:1.
[0025] (2) In-situ co-precipitation to obtain complex powder: Mix solution B with the obtained casein phosphopeptide (CPP) solution at room temperature and stir at 300-400 rpm until homogeneous. Using a constant flow pump or fine titration device, slowly and constantly add solution A to the mixture at a rate of 1-3 mL / min. This slow addition method is key to controlling the precipitation process and avoiding local supersaturation and rapid, disordered nucleation.
[0026] During the addition and stirring process, the pH value of the system was maintained in the range of 7.5-9.
[0027] Furthermore, using 1-3 mol·L -1 NaOH solution was used to adjust the pH of the reaction system.
[0028] Furthermore, after solution A has been added dropwise, continue stirring at 300-400 rpm for 2-4 hours to allow for maturation, ensuring a complete reaction and structural stability.
[0029] Further, the matured suspension is centrifuged at 20-30℃ and 3000-4000 rpm for 20-30 min, and the supernatant is discarded. The collected precipitate is resuspended and washed with sterile deionized water, and this process is repeated 1-5 times.
[0030] Furthermore, the washed precipitate is freeze-dried: placed under vacuum conditions of -80~-20℃ and 1-3 Pa, freeze-dried for 12-24 h to obtain a loosely structured CPP-ACP dry powder.
[0031] This invention precisely controls the co-precipitation process to a certain extent by controlling a gentle stirring rate and a slow dropping rate of the phosphate ion-containing solution, avoiding rapid deposition and uneven cluster structure caused by excessively high local ion concentrations. During this process, the guiding effect of 1,2-propanediol guides the slow and orderly growth of CPP-ACP, preventing spontaneous accumulation or aggregation, thus facilitating the final formation of a porous and loose cluster structure.
[0032] In one embodiment of the present invention, calcium chloride aqueous solution B and dipotassium hydrogen phosphate aqueous solution A are prepared. Solution B is mixed with casein phosphopeptide (CPP) solution and stirred. Then, solution A is slowly added dropwise to the mixture at a Ca:P ratio of 2:1, using 1 mol·L⁻¹ water. -1 The pH of the solution was adjusted to 9 with NaOH. After stirring with a magnetic stirrer for 2 h, the solution was centrifuged at 3000 rpm and 25 °C for 20 min. The supernatant was discarded, the precipitate was collected, washed, and freeze-dried at -70 °C and 1 Pa for 24 h to obtain casein phosphopeptide-amorphous calcium phosphate complex CPP-ACP dried powder.
[0033] (3) Preparation of carboxymethyl cellulose composite gel carrier: Disperse sodium carboxymethyl cellulose in water and swell to form a uniform sodium carboxymethyl cellulose slurry carrier.
[0034] Furthermore, the carboxymethyl cellulose slurry is obtained by dissolving carboxymethyl cellulose in water and stirring thoroughly.
[0035] Furthermore, the carboxymethyl cellulose raw material has a viscosity of 6000-12000 mPa•s and a degree of substitution of 0.75-0.8, making it more suitable for providing effective dispersion and support for CPP-ACP and nBG.
[0036] Furthermore, the carboxymethyl cellulose slurry has a carboxymethyl cellulose concentration of 5-15 mg / mL.
[0037] Furthermore, the slurry is sealed and stored at 0-4℃ for later use.
[0038] In one embodiment of the present invention, 1.25 g of sodium carboxymethyl cellulose powder is slowly added to 100 mL of distilled water at 50°C and heated. The mixture is stirred thoroughly and ultrasonically vibrated at 60 Hz and 30°C using an ultrasonic cleaner to ensure that the sodium carboxymethyl cellulose is evenly dispersed in the distilled water. The paste expands, dissolves, and becomes homogeneous. The mixed slurry is allowed to stand for 24 h to allow it to completely dissolve, thus completing the sodium carboxymethyl cellulose slurry. After sealing with sealing film, it is stored in a refrigerator at 4°C.
[0039] (4) Preparation of composite gel: CPP-ACP composite powder and nBG powder are added to carboxymethyl cellulose slurry and mixed evenly to prepare CPP-ACP / nBG composite gel.
[0040] The remineralized CPP-ACP / nBG composite gel prepared in this invention exhibits a porous cluster structure, a high Ca / P molar ratio, and retains the characteristic functional groups of CPP protein and nBG glass. Simultaneously, the rough surface of the composite gel with micropores facilitates ion release and penetration, improving remineralization efficiency. The Ca, P, Si, and O elements are uniformly distributed in the composite, and the functional groups are fused without disrupting their individual structures, suggesting stable chemical bonding or strong physical interactions. This results in a remineralized composite gel material with good bioactivity and structural stability, providing an effective basis for laser-assisted processing.
[0041] A third aspect of the present invention provides a composite gel as described in the first aspect or prepared by the preparation method described in the second aspect, for improving the mechanical properties of canine tooth enamel.
[0042] Furthermore, by combining CPP-ACP / nBG composite gel with laser treatment, the physiological mineralization structure of canine enamel can be restored without damaging the tooth structure, thereby improving mechanical properties and reducing the risk of dentin exposure.
[0043] Specifically, a method for combined laser treatment of CPP-ACP / nBG composite gel is provided, comprising the following steps: 1) Apply the composite gel to the enamel surface of the canine tooth and treat it at 30℃-40℃ for 20-60 min; remove excess composite gel from the enamel surface; 2) Use a diode laser to irradiate the treated enamel surface in pulse mode.
[0044] Further, in step 2), the laser intensity is 0.5W-6W, preferably 3-5W; the wavelength is 850-950 nm; and the pulse intensity is 10-20 Hz.
[0045] Preferably, the single irradiation time is 20-40 seconds, and the laser treatment cycle is 3-14 days.
[0046] In one embodiment of the present invention, CPP-ACP / nBG composite gel is applied to the enamel surface of a canine tooth using a dropper, ensuring even distribution. The surface is then remineralized at 37°C for 30 minutes, followed by rinsing with sterile deionized water. Subsequently, the enamel surface is irradiated using a 7 mm dental laser from a SUMMUS laser system. The irradiation parameters are pulse mode, laser wavelength 915 nm, frequency 15 Hz, irradiation time 30 s, and irradiation distance 5 mm. Simultaneously, a dental workbench is used to spray water onto the enamel surface for cooling.
[0047] The beneficial effects of this invention are: 1. This invention successfully constructed a porous cluster structure with a Ca / P molar ratio of approximately 1.93 by optimizing the ratio of CPP-ACP to nBG (preferably 10 wt% CPP-ACP and 6 wt% nBG) and combining it with an optimized in-situ co-precipitation process. This structure not only retains the active functional groups of each component but also exhibits uniform elemental distribution, forming a stable composite system. This provides an ideal ion source and nucleation sites for the efficient remineralization of the composite gel.
[0048] 2. This invention optimizes the coprecipitation process by controlling gentle stirring (300-400 rpm) and slow dropwise addition of phosphate solution (1-3 mL / min) to precisely regulate the coprecipitation kinetics. This ensures that CPP-ACP is deposited slowly in a controllable manner, effectively avoiding rapid and disordered nucleation caused by local supersaturation. This ensures that the product forms an ideal cluster morphology with uniform structure and well-developed pores, overcoming the defects of traditional methods that easily lead to coarse particles or dense structures. Moreover, after the coprecipitation reaction is completed, appropriate aging is performed to maintain the structure of the product, forming a stable porous cluster structure.
[0049] 3. This invention innovatively introduces a composite stabilizing system of glycerol and 1,2-propanediol, achieving multiple effects: In the enzymatic hydrolysis stage, the two can stabilize trypsin, ensuring the efficient preparation of CPP; in the co-precipitation stage, they can also act as structure directing agents to regulate interfacial energy, guiding the orderly stacking of CPP-ACP by regulating interfacial energy, directly participating in and stabilizing the porous and loose structure of the final product, effectively preventing spontaneous aggregation between components, and ensuring the uniformity and stability of the complex structure.
[0050] 4. The CPP-ACP / nBG composite gel prepared in this invention, with its porous cluster structure and high Ca / P ratio, provides continuous ion release while creating ideal synergistic conditions for combined laser treatment. The material's microstructure possesses excellent photothermal compatibility, uniformly absorbing and dispersing laser energy to ensure treatment safety. Its micro- and nano-pores act as "microreactors," where the gentle thermal effect generated by the laser promotes ion migration and accelerates the transformation of the amorphous phase into crystalline hydroxyapatite. Therefore, through the combined treatment steps of the composite gel material and laser, a synergistic effect of physical energy and chemical substances at the site of action is achieved, resulting in excellent remineralization without damaging tooth tissue. Attached Figure Description
[0051] Figure 1 This is a scanning electron microscope image of the composite gel (10% CPP-ACP / 6% nBG) from Example 1.
[0052] Figure 2 The image shows the FTIR spectrum of the composite gel (10% CPP-ACP / 6% nBG) from Example 1.
[0053] Figure 3 The SEM images of the enamel surface after treatment with composite gel combined with different laser intensities in Example 2 are shown. A is group 1, B is group 2, C is group 3, D is group 4, E is group 5, F is group 6, G is group 7, H is group 8, I is group 9, and J is group 10. Detailed Implementation
[0054] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0055] The reagents and raw materials used in the embodiments of this invention are all commercially available.
[0056] Example 1 A CPP-ACP / nBG composite gel for remineralization of canine enamel includes the following steps: (1) Preparation of casein phosphopeptide-amorphous calcium phosphate complex (CPP-ACP): S1. Enzymatic hydrolysis of casein solution to obtain casein phosphopeptide (CPP) solution: Dissolve 25g of casein in 250mL of distilled water, adjust the pH of the system to 8, add 2g of trypsin, stir, and incubate at 45℃ for 12 h. After enzymatic hydrolysis, adjust the pH to 4.0-4.8, and a precipitate will appear in the solution; centrifuge at 3000rpm, 25℃ for 20min, collect the precipitate, and dissolve it in sterile deionized water to prepare a 10% w / v casein solution.
[0057] S2. Prepare solutions A containing calcium ions and B containing phosphate ions respectively: Weigh 13.87 g (0.12 mol) of anhydrous calcium chloride solid and dissolve it in sterile deionized water to form solution B; weigh 8.87 g (0.06 mol) of dipotassium hydrogen phosphate solid and dissolve it in sterile deionized water to form solution A.
[0058] (2) In-situ co-precipitation to obtain complex powder: The prepared solution B and the obtained casein phosphopeptide (CPP) solution were mixed at room temperature and placed on a magnetic stirrer. The mixture was stirred at a medium speed of 300 rpm to ensure uniform mixing. Solution A was added dropwise to the above mixture at a slow and constant rate of 2 mL / min using a constant flow pump, maintaining the pH at 8.5. After the addition of solution A was complete, the mixture was stirred at 300 rpm for 2 h to allow it to mature. Then, the mixture was centrifuged at 3000 rpm and 25°C for 20 min. The supernatant was discarded, and the precipitate was washed with sterile deionized water. The washing was repeated 3 times. The mixture was then freeze-dried at -70°C and 2 Pa for 24 h to obtain CPP-ACP dry powder.
[0059] (3) Preparation of composite gel carrier: 1.25 g of carboxymethyl cellulose powder (viscosity 6000-12000 mPa•s, degree of substitution 0.75~0.8) was dissolved in 100 mL of distilled water at 50℃. The mixture was stirred thoroughly and ultrasonically vibrated at 60 Hz and 30℃ using an ultrasonic cleaner to make sodium carboxymethyl cellulose evenly dispersed in distilled water. The paste swelled and dissolved, and was in a uniform state. The mixed slurry was left to stand for 24 h to completely dissolve, and sodium carboxymethyl cellulose slurry was obtained. After sealing with sealing film, it was stored in a refrigerator at 4℃.
[0060] (4) Preparation of composite gel: Weigh an appropriate amount of dry CPP-ACP powder and nBG powder, add them slowly to the prepared sodium carboxymethyl cellulose slurry in small amounts multiple times at room temperature, and use an ultrasonic cleaner to ultrasonically vibrate and mix them to prepare a CPP-ACP / nBG composite gel containing 10% CPP-ACP and 6% nBG. After sealing with sealing film, store in a refrigerator at 4℃.
[0061] Morphology and characterization of the composite gel: The prepared CPP-ACP / nBG gel samples were pre-frozen in an ultra-low temperature freezer at -80℃, and then freeze-dried. After grinding, the freeze-dried products were characterized and analyzed by SEM-EDS.
[0062] The morphology of the CPP-ACP-nBG composite gel was observed using scanning electron microscopy, and the results are as follows: Figure 1 As shown. Scanning electron microscopy results show that the material has a clustered, irregular block structure with a rough surface, obvious wrinkles and pores, exhibiting typical porous characteristics. (Low magnification) Figure 1 A) It can be seen that the complex particles are of varying sizes and exhibit a loosely aggregated state; under high magnification ( Figure 1 B) Further analysis reveals a complex surface microstructure with cracks and interparticle channels. This porous structure facilitates close contact between the material and the enamel surface, while providing a sufficient reaction interface to promote Ca2+ reaction. 2+ PO4 3- The release and permeation of remineralized ions.
[0063] The freeze-dried CPP-ACP / nBG porous solid was finely ground into a uniform powder using a mortar and pestle. The sample was then analyzed using a Thermo Fisher Nicolet iS50 Fourier Transform Infrared Spectroscopy (FTIR) instrument in the range of 4000–4000 cm⁻¹. -1 Detection was performed within the wavenumber range, and the functional group structure and molecular bonding characteristics were characterized by analysis of characteristic absorption peaks. The chemical structure and functional group configuration of the composite material are shown in the FTIR results of CPP-ACP (the product of step 2), nBG, and its composite CPP-ACP / nBG. Figure 2 As shown.
[0064] 3487 cm was observed in the CPP-ACP sample. -1 The OH stretching vibration peak at 1216 cm⁻¹ -1 CN bond and 1122cm -1 The PO absorption peak indicates that it possesses a typical organophosphorus protein structure; a 1031 cm⁻¹ peak was observed in the nBG sample. -1 The characteristic peaks of Si-O-Si, and C=O (1645 cm⁻¹) -1 ) and CO (1441 cm -1 The absorption peak is consistent with typical spectra of bioactive glass. Notably, the nBG sample shows an absorption peak at 1441 cm⁻¹. -1 The peak at 1031 cm⁻¹ shows a symmetric stretching vibration of the CO bond in the carbonate ion, while at 1031 cm⁻¹...-1 The presence of a distinct Si-O-Si asymmetric stretching vibration peak (characteristic of silicate framework) indicates that it retains the structural properties of nBG. However, in the FTIR spectrum of the composite material, the peak at 1031 cm⁻¹ is not significant. -1 The Si-O characteristic peaks at 1122 cm⁻¹ did not appear independently, and combined with CPP-ACP, the peaks at 1122 cm⁻¹ were not observed independently. -1 The strong PO bond vibration peak at 1645 cm⁻¹ suggests that during the recombination process, the Si-O bond vibration peak of nBG is shifted or weakened due to overlap with the CO bond peak in CPP-ACP. This implies that the two phases may form chemical interactions through hydroxyl or phosphate groups, thus affecting the independent characterization of characteristic peaks. Furthermore, the CPP-ACP / nBG mixture exhibits a strong PO bond vibration peak at 1645 cm⁻¹. -1 The significant absorption peak of the C=O bond is still retained at this point, while nBG has an absorption peak of 1441 cm⁻¹. -1 The peaks in the mixture are weakened but still identifiable, indicating that the carbonate ions of nBG partially participate in the complexation reaction, but still exist in the system in the form of physical blending.
[0065] Furthermore, Table 1 shows the quantitative analysis results of each element in the complex. The mass percentages of O, Ca, P, and Si are 60.28%, 15.00%, 5.95%, and 14.52%, respectively, with corresponding atomic percentages of 76.01%, 7.48%, 3.87%, and 10.43%. The Ca / P molar ratio is approximately 1.93, slightly higher than that of physiological tooth enamel (1.67), indicating that the complex may exist in the form of amorphous calcium phosphate or a calcium-rich phase, which is conducive to the formation of a stable apatite structure during subsequent remineralization.
[0066] Table 1. Elemental quantitative analysis of the composite gel (10% CPP-ACP / 6% nBG) in Example 1 .
[0067] In summary, the 10% CPP-ACP / 6% nBG composite gel exhibits a porous cluster structure with a rough surface and micropores, which facilitates ion release and penetration, thereby improving remineralization efficiency. The Ca, P, Si, and O elements are evenly distributed, and the functional groups are integrated without compromising their individual structures. The high Ca / P molar ratio results in a composite gel material with good bioactivity and structural stability.
[0068] Example 2 Steps (1)-(3) are the same as in Example 1, except that: (4) Preparation of composite gel: Weigh an appropriate amount of dry CPP-ACP powder and nBG powder, add them slowly to the prepared sodium carboxymethyl cellulose slurry in small amounts multiple times at room temperature, and use an ultrasonic cleaner to ultrasonically vibrate and mix them to prepare a CPP-ACP / nBG composite gel containing 10% CPP-ACP and 3% nBG. After sealing with sealing film, store in a refrigerator at 4℃.
[0069] Example 3 Steps (1)-(3) are the same as in Example 1, except that: (4) Preparation of composite gel: Weigh an appropriate amount of dry CPP-ACP powder and nBG powder, add them slowly to the prepared sodium carboxymethyl cellulose slurry in small amounts multiple times at room temperature, and use an ultrasonic cleaner to ultrasonically vibrate and mix them to prepare a CPP-ACP / nBG composite gel containing 10% CPP-ACP and 9% nBG. After sealing with sealing film, store in a refrigerator at 4℃.
[0070] Example 4 Steps (2)-(4) are the same as in Example 1, except that: (1) Preparation of casein phosphopeptide-amorphous calcium phosphate complex (CPP-ACP): S1. Dissolve 25g of casein in 250mL of distilled water, adjust the pH of the system to 8, add 2g of trypsin, 0.1mL of glycerol and 0.05mL of 1,2-propanediol, stir and place in a 45℃ incubator for enzymatic hydrolysis for 12 h. After enzymatic hydrolysis, adjust the pH to 4.0-4.8, and a precipitate will appear in the solution; centrifuge at 3000rpm, 25℃ for 20min, collect the precipitate, and dissolve it in sterile deionized water to prepare a 10% w / v casein solution.
[0071] S2. Weigh 13.87 g (0.12 mol) of anhydrous calcium chloride solid and dissolve it in sterile deionized water to form solution B; weigh 8.87 g (0.06 mol) of dipotassium hydrogen phosphate solid and dissolve it in sterile deionized water to form solution A.
[0072] Example 5 Steps (1), (3), and (4) are the same as in Example 1, except that: (2) In-situ co-precipitation to obtain complex powder: The prepared solution B and the obtained casein phosphopeptide (CPP) solution were mixed at room temperature and placed on a magnetic stirrer at 800 rpm to ensure uniform mixing. Solution A was added dropwise to the above mixture at a constant rate of 5 mL / min using a constant flow pump, maintaining the pH at 8.5. After the addition of solution A was complete, stirring was continued at 800 rpm for 2 h for maturation. Then, the mixture was centrifuged at 3000 rpm and 25 °C for 20 min, the supernatant was discarded, the precipitate was collected, and washed with sterile deionized water, repeating the washing process 3 times. The mixture was then freeze-dried at -70 °C and 2 Pa for 24 h to obtain CPP-ACP dried powder.
[0073] Example 6 Steps (2)-(4) are the same as in Example 4, except that: (1) Preparation of casein phosphopeptide-amorphous calcium phosphate complex (CPP-ACP): S1. Dissolve 25g of casein in 250mL of distilled water, adjust the pH of the system to 8, add 2g of trypsin, 0.15mL of glycerol and 0.05mL of 1,2-propanediol, stir and place in a 40℃ incubator for enzymatic hydrolysis for 12 h. After enzymatic hydrolysis, adjust the pH to 4.0-4.8, and a precipitate will appear in the solution; centrifuge at 3000rpm, 25℃ for 20min, collect the precipitate, and dissolve it in sterile deionized water to prepare a 10% w / v casein solution.
[0074] S2. Weigh 13.87 g (0.12 mol) of anhydrous calcium chloride solid and dissolve it in sterile deionized water to form solution B; weigh 8.87 g (0.06 mol) of dipotassium hydrogen phosphate solid and dissolve it in sterile deionized water to form solution A.
[0075] Example 7 All other steps are the same as in Example 1, with the only difference being: (1) Preparation of casein phosphopeptide-amorphous calcium phosphate complex (CPP-ACP): S1. Dissolve 25g of casein in 250mL of distilled water, adjust the pH of the system to 8, add 2g of trypsin and 0.1mL of glycerol, stir, and incubate at 45℃ for 12 h. After enzymatic hydrolysis, adjust the pH to 4.0-4.8, and a precipitate will appear in the solution; centrifuge at 3000rpm, 25℃ for 20min, collect the precipitate, and dissolve it in sterile deionized water to prepare a 10% w / v casein solution.
[0076] Comparative Example 1 Steps (1)-(3) are the same as in Example 1, except that: (4) Preparation of composite gel: Weigh an appropriate amount of dry CPP-ACP powder and slowly add it to the prepared sodium carboxymethyl cellulose slurry in small amounts at room temperature. Use an ultrasonic cleaner to ultrasonically vibrate and mix it to prepare a CPP-ACP composite gel containing 10% CPP-ACP. After sealing with sealing film, store it in a refrigerator at 4°C.
[0077] Application Example 1: Treatment of Composite Gel Alone The prepared remineralization composite gel was used in the remineralization treatment of canine enamel: Canine teeth of the same species were coated with the composite gel prepared in the examples and comparative examples for 72 h, and the changes in the mechanical properties of the enamel of different samples were compared (Approval number of Experimental Animal Welfare and Animal Experiment Ethics of China Agricultural University: AW90605202-2-05).
[0078] Group 1: Canine teeth extracted from the canine mouth, after being polished, were immersed in artificial saliva and stored in a 37°C incubator for 72 hours, which is the normal canine enamel group.
[0079] Group 2: Normal canine enamel samples were immersed in a demineralization solution (0.24 g anhydrous calcium chloride, 0.30 g potassium dihydrogen phosphate, and 2.87 mL acetic acid were weighed, stirred and dissolved at room temperature, and the pH of the demineralization solution was adjusted to 4.8. After preparation, the solution was stored in a 4°C refrigerator) and demineralized in a 37°C incubator for 72 h; this was the demineralized enamel group.
[0080] Group 3: The surface of the demineralized enamel samples was coated with the composite gel of Example 1 and kept for 72 h.
[0081] Groups 4-9: The composite gel of Examples 2-7 was coated on the surface of the demineralized enamel samples and kept for 72 h.
[0082] Group 10: The surface of the demineralized enamel samples was coated with the gel material of Comparative Example 1 and kept for 72 h.
[0083] The mechanical property testing method was as follows: Samples from each group were embedded, and quasi-static nanoindentation tests were performed on the enamel using the Clarisse iMicro nanoindenter. Five points were selected for each sample, and the indentation conditions were set to a maximum load of 15 mN. The main performance indicators of canine enamel after treatment with different gel samples, such as nano-strength, elastic modulus, and Ca / P molar ratio, are shown in Table 2.
[0084] Table 2. Changes in the mechanical properties of demineralized tooth enamel treated with different gels. .
[0085] As shown in Table 2, the repair effect (hardness: 1.06 GPa, Ca / P ratio: 1.33) of Example 1 (10% CPP-ACP / 6% nBG) was significantly better than that of Comparative Example 1 (10% CPP-ACP only) (hardness: 0.59 GPa, Ca / P ratio: 1.09), demonstrating that the addition of nBG significantly improved remineralization capacity. Examples 4 and 6 achieved the best repair effects, with the highest nano-hardness (~1.17-1.20 GPa) and Ca / P ratio (~1.38-1.40) among all treatment groups, indicating that the composite stabilizer helps to form a better mineral structure. Example 5 may have had a limited improvement in hardness (0.87 GPa) due to the excessively fast deposition rate, which affected the orderly deposition of minerals. Example 7 used glycerol as a single stabilizer, and its effect (hardness: 0.91 GPa) was not as good as that of Examples 4 and 6, which used a composite stabilizer, indicating that the stabilizer system has an important impact on performance.
[0086] Application Example 2: Composite Gel Combined with Laser Treatment The prepared remineralization composite gel, combined with laser treatment, was used in the remineralization treatment of canine enamel: 1) The composite gel was applied to the surface of canine enamel, ensuring uniform distribution, and remineralized for 30 min in a 37℃ incubator, followed by rinsing with sterile deionized water; 2) A 7 mm dental SUMMUS laser (wavelength 915 nm) was used in pulse mode (15 Hz), with a single irradiation time of 30 s, a fixed irradiation distance of 5 mm, a laser intensity of 0.5-7.0 W, and a remineralization cycle of 7 days; the effect of different laser intensities on canine enamel treatment was investigated.
[0087] Group 1: Normal canine enamel group, serving as the benchmark for ideal mechanical properties and surface morphology.
[0088] Group 2: Demineralized enamel group, which is a demineralized enamel sample after being treated with an acidic solution from a normal enamel group sample, used as the baseline for the pathological model that needs to be repaired (the demineralization process is the same as Group 2 in Application Example 1).
[0089] Group 3: The composite gel of Example 1 was applied only to the surface of the demineralized enamel samples, and the samples were remineralized for 7 days without laser irradiation.
[0090] Group 4: The surface of the demineralized enamel samples was treated with the composite gel of Example 1, combined with 0.5 W laser intensity treatment, and remineralized for 7 days.
[0091] Group 5: The surface of the demineralized enamel samples was treated with the composite gel of Example 1, combined with 1.0 W laser intensity treatment, and remineralized for 7 days.
[0092] Group 6: The surface of the demineralized enamel samples was treated with the composite gel of Example 1, combined with 1.5 W laser intensity treatment, and remineralized for 7 days.
[0093] Group 7: The surface of the demineralized enamel samples was treated with the composite gel of Example 1, combined with 3W laser intensity treatment, and remineralized for 7 days.
[0094] Group 8: The surface of the demineralized enamel samples was treated with the composite gel of Example 1, combined with 5W laser intensity treatment, and remineralized for 7 days.
[0095] Group 9: The surface of the demineralized enamel samples was treated with the composite gel of Example 1, combined with 6W laser intensity treatment, and remineralized for 7 days.
[0096] Group 10: The surface of the demineralized enamel samples was treated with the composite gel of Example 1, combined with 7W laser intensity treatment, and remineralized for 7 days.
[0097] Group 11: The surface of the demineralized enamel samples was treated with the composite gel of Example 4, combined with 5W laser intensity treatment, and remineralized for 7 days.
[0098] Group 12: The surface of the demineralized enamel samples was treated with the composite gel of Example 5, combined with 5W laser intensity treatment, and remineralized for 7 days.
[0099] Group 13: The surface of the demineralized enamel samples was treated with the composite gel of Example 6, combined with 5W laser intensity treatment, and remineralized for 7 days.
[0100] Group 14: The surface of the demineralized enamel samples was treated with the composite gel of Example 7, combined with 5W laser intensity treatment, and remineralized for 7 days.
[0101] To evaluate the restorative effect of CPP-ACP / nBG composite gel (prepared in the examples) combined with laser irradiation of different intensities on demineralized enamel, the treated samples underwent nanomechanical property testing, elemental analysis, and comprehensive characterization using SEM images. The results are shown in Table 3. Figure 3 As shown.
[0102] The mechanical property testing method was as follows: each group of samples was embedded, and a quasi-static nanoindentation test was performed on the enamel using the iMicro nanoindenter from Clarex Corporation, USA. Five points were selected for each sample, and the indentation conditions were the maximum load of 15mN. The results are shown in Table 3.
[0103] Elemental analysis was performed using EDS: the aperture was set to 120 µm, and Ca and P signals of normal and demineralized enamel were acquired at 1000x magnification. Ca and P signals of enamel from each treatment group were acquired at 3000x magnification. The elemental content of Ca and P on the surface of each sample and the Ca / P molar ratio were tested and recorded. The results are shown in Table 3.
[0104] Table 3. Effects of composite gel combined with different laser intensities on tooth enamel. .
[0105] As shown in Table 3, demineralization treatment (group 2) caused a sharp decrease in the nano-hardness and elastic modulus of enamel, significantly lower than that of the normal group (group 1), successfully establishing a demineralization model. Using the composite gel alone (group 3) partially restored the mechanical properties, but there was still a significant difference compared to the normal group.
[0106] When the composite gel was combined with laser irradiation, the mechanical properties of tooth enamel were significantly improved, and this improvement was clearly dependent on the laser intensity. As the laser intensity increased from 0.5 W to 5.0 W, the degree of recovery of nano-hardness and elastic modulus generally showed an upward trend. Most importantly, group 8 (composite gel + 5.0 W laser) showed the most outstanding repair effect, with its nano-hardness (3.10±0.67 GPa) and elastic modulus (101.20±11.69 GPa) both recovering to levels similar to the normal group (3.90±0.42 GPa, 103.50±2.42 GPa). This indicates that 5.0 W is the optimal laser parameter for achieving the best recovery of tooth enamel mechanical properties under the experimental conditions. However, when the laser intensity exceeded 5.0 W, the repair effect decreased. The nano-hardness of group 9 (composite gel + 6.0 W) declined, while the hardness and modulus of group 10 (composite gel + 7.0 W) both decreased.
[0107] Furthermore, compared to Example 1, when using the optimized composite gels of Examples 4 and 6, the efficient CPP preparation process ensured the orderly stacking of CPP-ACP, effectively preventing component aggregation and thus ensuring the uniformity and stability of the composite structure. Based on this, combined laser treatment produced a significant synergistic enhancement effect, further improving nanoscale hardness and elastic modulus, fully validating the effectiveness of the optimized preparation process. In Example 5, due to the excessively rapid co-precipitation process, the composite was prone to local aggregation, resulting in insufficient structural uniformity. Therefore, even with combined laser treatment, its remineralization effect (mechanical properties) decreased. Similarly, Example 7, using only glycerol as a protectant, had limited improvement in enzyme activity efficiency, leading to minimal performance improvement after combined laser treatment.
[0108] The above results confirm a significant synergistic effect between CPP-ACP / nBG composite gel and laser irradiation. The mechanism lies in the photothermal effect generated by appropriate laser energy. On the one hand, it accelerates the release and migration of calcium and phosphorus ions in the composite gel; on the other hand, it provides activation energy to the enamel surface, lowering the energy barrier for hydroxyapatite nucleation and crystallization. This guides the minerals to deposit in a more ordered and dense manner, achieving a strong bond with the matrix. However, excessively high laser intensity generates heat energy exceeding the tolerance threshold of tooth enamel, causing tissue damage and potentially reducing the effectiveness of remineralization treatment.
[0109] Microscopic morphology analysis: Three enamel embedding blocks from each group were randomly selected for SEM and EDS analysis. The embedding blocks were sequentially placed in ethanol solutions of varying concentrations (30%, 50%, 70%, 80%, 90%, and 100%) for dehydration, with each concentration lasting 10 min, and then allowed to air dry at room temperature. To avoid interference from metal sputtering on Ca and P elemental analysis, carbon sputtering was used. Scanning electron microscopy was performed at an accelerating voltage of 15 kV, a grid aperture size of 30 µm, and at 3000x magnification to observe the remineralization morphology of the enamel surface.
[0110] Among them, SEM images of the enamel surface after treatment in groups 1-10 are as follows: Figure 3 As shown in the figure. Among them, A is the SEM image of group 1, B is the SEM image of group 2, C is the SEM image of group 3, D is the SEM image of group 4, E is the SEM image of group 5, F is the SEM image of group 6, G is the SEM image of group 7, H is the SEM image of group 8, I is the SEM image of group 9, and J is the SEM image of group 10.
[0111] Through the Figure 3 Comparative analysis of SEM images from different groups clearly shows the effect of laser intensity on the morphology and structure of the remineralized layer: In group 3, where no laser irradiation was used, only sparse and discontinuous mineral deposits were visible on the enamel surface. These deposits failed to effectively cover the micropores formed by demineralization, indicating that simple chemical remineralization has some effect, but its effect is limited. As the laser intensity increased to 1.0-3.0 W (groups 5-7), the surface deposits increased significantly and became more densely distributed, beginning to form irregular cluster-like covering layers, showing the promoting effect of laser energy on mineral deposition. In the figure, the yellow arrows point to the micropores formed by demineralization on the enamel surface; the red triangles point to the irregular mineral deposits formed on the enamel surface after remineralization; the white dashed circle area represents the "melting" traces under high-intensity laser irradiation.
[0112] Notably, group 8 (5.0 W) exhibited the best remineralization effect, forming a uniform, dense remineralized layer on its surface that was well integrated with the underlying glaze. This unique "fused" structure (white dashed circle) effectively transfers and disperses stress, which is the microstructural basis for the optimal recovery of the mechanical properties of this group. Meanwhile, this group achieved a Ca / P molar ratio of 1.54, closest to the normal glaze's 1.57, further confirming the superiority of its mineral composition.
[0113] However, when the laser intensity was further increased to 6.0-7.0 W (groups 9-10), the SEM images clearly showed the thermal damage characteristics caused by the excessively strong laser. Figure 3 The red dashed line in -I indicates the presence of cracks and the formation of burn pits; Figure 3 The yellow dashed circle in -J indicates numerous irregular fragments on the enamel surface. This structural damage directly explains the deterioration of mechanical properties in these groups, despite their Ca / P ratio remaining at a high level. These morphological observations are in high agreement with the aforementioned mechanical property data and elemental analysis results, jointly confirming that 5.0 W is the ideal laser parameter for achieving optimal remineralization.
[0114] The experimental data above indicate that, based on mechanical property tests, group 8, treated with a 5.0 W laser combined with CPP-ACP / nBG remineralization, exhibited mechanical properties close to those of normal enamel in group 1, demonstrating superior restorative effects compared to other groups. This resulted in a more continuous remineralized coating with higher roughness and a more homogeneous, fused deposit, forming a stronger protective layer. Crystal melting and directional recrystallization occurred on the material surface, leading to rapid changes in the enamel surface structure. Groups 3-7 showed that while using CPP-ACP / nBG composite gel alone or in combination with low-intensity laser could slightly improve the mechanical properties of enamel, the effect was limited; in contrast, the mechanical properties of groups 9 and 10 decreased.
Claims
1. A composite gel for remineralizing canine enamel, characterized in that, The composite gel comprises casein phosphopeptide-amorphous calcium phosphate and active nanoglass; The composite gel contains 5-15 wt% casein phosphopeptide-amorphous calcium phosphate and 3-10 wt% active nanoglass. The composite gel has a porous cluster structure, wherein the Ca / P molar ratio is 1.8-2:
1.
2. A method for preparing a composite gel for remineralizing canine tooth enamel, characterized in that, Includes the following steps: (1) Preparation of casein phosphopeptide-amorphous calcium phosphate complex: S1. Enzymatically hydrolyze casein solution to obtain casein phosphopeptide solution; S2. Prepare solution A containing calcium ions and solution B containing phosphate ions respectively; (2) In-situ co-precipitation yielded the composite powder: Mix solution B with the obtained casein phosphopeptide solution at room temperature and stir at 300-400 rpm until homogeneous; add solution A to the mixture slowly and at a constant rate of 1-3 mL / min using a constant flow pump or fine titration device. Preparation of carboxymethyl cellulose composite gel carrier; Preparation of composite gel: Casein phosphopeptide-amorphous calcium phosphate complex powder and active nano glass powder are added to the carrier slurry and mixed evenly to prepare composite gel.
3. The preparation method according to claim 2, characterized in that, In step S1, casein is dissolved in water, the pH is adjusted to 7-9, and trypsin is added for enzymatic hydrolysis. After enzymatic hydrolysis, the pH is adjusted to 4.0-4.8, a precipitate appears, and after centrifugation, an 8%-15% w / v casein solution is obtained.
4. The preparation method according to claim 3, characterized in that, The concentration of the casein aqueous solution is 80-120 mg / mL, the enzymatic hydrolysis temperature is 35-50℃, and the enzymatic hydrolysis time is 8-16 h; the amount of trypsin added is 5-10 wt% of the casein.
5. The preparation method according to claim 3, characterized in that, The enzymatic hydrolysis process involves the addition of glycerol and 1,2-propanediol, wherein the amount of glycerol added is 5-10 wt% of trypsin, and the amount of 1,2-propanediol added is 1-3 wt% of trypsin.
6. The preparation method according to claim 2, characterized in that, In step S2, solution A is one or more of potassium dihydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate aqueous solution; solution B is one or more of calcium chloride, calcium nitrate, and calcium sulfate aqueous solution. The calcium / phosphorus (Ca / P) molar ratio in solution A and solution B is 2:
1. In step (2), the pH value of the system is maintained at 7.5-9.
7. The preparation method according to claim 2, characterized in that, Step (3) Disperse sodium carboxymethyl cellulose in water and swell to form a uniform sodium carboxymethyl cellulose slurry carrier; The carboxymethyl cellulose raw material has a viscosity of 6000-12000 mPa•s and a degree of substitution of 0.75-0.
8. In the carboxymethyl cellulose slurry, the concentration of carboxymethyl cellulose is 5-15 mg / mL.
8. The composite gel according to claim 1 or the composite gel obtained by the preparation method according to any one of claims 2-7, in the field of enamel remineralization.
9. A method for combined laser treatment with composite gel, comprising the following steps: 1) Apply the composite gel of claim 1 or the composite gel prepared by any one of claims 2-7 to the enamel surface of a canine tooth, treat it at 30℃-40℃ for 20-60 min, and remove the excess composite gel from the enamel surface. 2) Use a diode laser to irradiate the treated enamel surface in pulse mode.
10. The processing method according to claim 9, characterized in that, In step 2), the laser intensity is 0.5-6 W, preferably 3-5 W; the wavelength is 850-950 nm; and the pulse intensity is 10-20 Hz. The duration of a single irradiation is 20-40 seconds, and the laser treatment cycle is 3-14 days.